2022
DOI: 10.31004/cendekia.v6i2.1024
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kemampuan Pemecahan Masalah Barisan dan Deret Berdasarkan Asimilasi dan Akomodasi Pada Gaya Kognitif Reflektif dan Impulsif

Abstract: Salah satu kemampuan yang dikembangkan dalam pembelajaran matematika adalah kemampuan pemecahan masalah. Siswa sudah mampu mengerjakan soal matematika tetapi belum cukup baik dalam menganalisis dan berpikir dengan maksimal. Sehingga menyebabkan rendahnya kemampuan pemecahan masalah matematika siswa. Hal ini juga di sebabkan karena adanya perbedaan gaya kognitif pada masing masing siswa. Penelitian ini bertujuan untuk mendeskripsikan kemampuan pemecahan masalah barisan dan deret pada gaya kognitif reflektif dan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
0
3
0
3
Order By: Relevance
“…This was confirmed from the results of interviews which showed that the respondents had no difficulty in reading the questions because the instructions for working on the questions were very clear and in order. Putri (2021) revealed that both respondents who have reflective cognitive abilities and impulsive cognitive abilities both have the ability to understand reading questions well. Second, the analysis of errors in understanding the problem.…”
Section: Resultsmentioning
confidence: 99%
“…This was confirmed from the results of interviews which showed that the respondents had no difficulty in reading the questions because the instructions for working on the questions were very clear and in order. Putri (2021) revealed that both respondents who have reflective cognitive abilities and impulsive cognitive abilities both have the ability to understand reading questions well. Second, the analysis of errors in understanding the problem.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, this geometric Sequence and series problem can be applied to solve everyday problems, so it is very suitable to be used to determine students' problem solving skills (Rambe & Afri, 2020). One of the efforts to improve mathematical problem solving skills on the material of Sequence and series is to apply a learning model that makes the role of students more dominant and students work more with various knowledge so that students can understand the concepts given in their own way and understanding (Putri & Huda, 2022). Sequence and series topic is very suitable to be delivered through learning with a project-based learning model (Pamungkas et al, 2019).…”
Section: Can't Remember Math Problem Like I Can Remember Formulasmentioning
confidence: 99%
“…Hotel adalah sebuah tempat yang menyediakan pelayanan akomodasi, biasanya untuk jangka waktu yang singkat, kepada para tamu yang membayar. Hotel biasanya memiliki sejumlah kamar tidur yang dilengkapi dengan fasilitas seperti tempat tidur, kamar mandi pribadi, televisi, telepon, dan akses internet (Putri, 2018). Selain itu, hotel juga biasanya menyediakan layanan tambahan seperti restoran, bar, kolam renang, pusat kebugaran, layanan kamar, ruang pertemuan, dan fasilitas lainnya untuk memenuhi kebutuhan dan kenyamanan para tamu.…”
Section: Pendahuluanunclassified